Faktor Risiko Kejadian Psoriasis pada Pasien Rawat Jalan di RS Royal Prima Medan: Studi Case-Control - Guo Xinyuan; Tri Suci; Liena Liena; Fioni Fioni (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Psoriasis is a chronic immune-mediated inflammatory disease characterized by keratinocyte hyperproliferation and persistent systemic inflammation, and is associated with genetic predisposition and metabolic comorbidities. Identifying its determinants is important to improve prevention and clinical management. This study aimed to analyze the association between age, body mass index (BMI), smoking history, family history of psoriasis, diabetes mellitus, and hypertension with the occurrence of psoriasis in outpatients at the Dermatology and Venereology Clinic of Royal Prima Hospital, Medan, from 2024 to 2025. This study used an analytical observational design with a retrospective case-control approach. A total of 210 respondents were included, consisting of 105 cases (patients diagnosed with psoriasis) and 105 controls (patients without psoriasis). Controls were selected from patients attending the same clinic during the same period without a diagnosis of psoriasis to ensure comparability and minimize selection bias. Data were obtained from medical records and analyzed using the Chi-square test and binary logistic regression. Bivariate analysis showed that age ≥45 years, BMI ≥25 kg/m², smoking history, family history of psoriasis, diabetes mellitus, and hypertension were significantly associated with psoriasis (p < 0.05). Multivariate analysis revealed that age ≥45 years (Adjusted OR = 1.85; 95% CI: 1.02–3.35; p = 0.042), BMI ≥25 kg/m² (Adjusted OR = 1.98; 95% CI: 1.09–3.61; p = 0.024), family history of psoriasis (Adjusted OR = 6.45; 95% CI: 2.82–14.75; p < 0.001), and diabetes mellitus (Adjusted OR = 2.41; 95% CI: 1.05–5.54; p = 0.037) remained significant predictors. Family history of psoriasis was identified as the most dominant determinant. These findings highlight the importance of early screening in high-risk individuals, particularly those with a family history of psoriasis and metabolic comorbidities, to support timely detection and improve clinical management. In conclusion, genetic and metabolic factors, along with age, are key determinants of psoriasis occurrence.